Surveying Pornography Use: A Shaky Science Resting on Poor Measurement Foundations. Issue 6 (23rd July 2020) - Kohut, Taylor; Balzarini, Rhonda N.; Fisher, William A.; Grubbs, Joshua B.; Campbell, Lorne; Prause, Nicole
ABSTRACT: A great deal of pornography research relies on dubious measurements. Measurement of pornography use has been highly variable across studies and existing measurement approaches have not been developed using standard psychometric practices nor have they addressed construct validation or reliability. This state of affairs is problematic for the accumulation of knowledge about the nature of pornography use, its antecedents, correlates, and consequences, as it can contribute to inconsistent results across studies and undermine the generalizability of research findings. This article provides a summary of contemporary measurement practices in pornography research accompanied by an explication of the problems therein. It also offers suggestions on how best to move forward by adopting a more limited set of standardized and validated instruments. We recommend that the creation of such instruments be guided by the careful and thorough conceptualization of pornography use and systematic adherence to measurement development principles.